Solar Hybrid Heating & Cooling Systems on District Level – The Austrian Project CiQuSo. (June 2016) - Horn, Philip; Hauer, Stefan; Judex, Florian; Kreulitsch, David; Selke, Tim
Abstract: The Austrian research project City quarters with optimised solar hybrid heating and cooling systems-. (CiQuSo) aims to develop, evaluate and optimize concepts for solar energy systems to provide energy for buildings and cities. The comparison and alignment of the energy demand (heating, cooling, domestic hot water, electricity) with the production in terms of dynamic behavior and spatial distribution enables the optimization of the energy performance of a district or a small city. Based on solar thermal and solar electrical systems highly innovative solar hybrid concepts (based on the assumption of possible energy exchange between certain or all buildings in the district) will be developed and will be applied in Heating, Ventilation and Air Conditioning- (HVAC) systems for buildings. The applications will be evaluated on city district level in order to identify further optimization potentials gained by the intra-building energy exchange as well as load shifting strategies. The applicability of the developed methods and concepts will be tested in Itzling, a district in the city of Salzburg, Austria. This paper presents the planned methodology to optimize the use of solar energy on a district level and will reports on first achievements of the project activities.